2006 IEEE 4th World Conference on Photovoltaic Energy Conference 2006
DOI: 10.1109/wcpec.2006.279718
|View full text |Cite
|
Sign up to set email alerts
|

2D-Modeling and Development of Interdigitated Back Contact Solar Cells on Low-Cost Substrates

Abstract: Two-dimensional numerical simulations were performed to derive design rules for low-cost, high-efficiency interdigitated back contact (IBC) solar cells on a low-cost substrate. The IBC solar cells were designed to be fabricated using either the conventional screen printing or photolithography metallization processes. Bulk lifetime, bulk resistivity, contact spacing (pitch), contact opening width, recombination in the gap between the p + BSF and n + emitter, and the ratio of emitter width to pitch have been use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Renshaw et al [8] reported the η trend as a function of doping peaks for front surface field (FSF), back surface field (BSF) and emitter. Kim et al [9] studied some FOM as a function of geometrical parameters. In both works, FOM trends are evaluated for different surface recombination velocities (SRV) and bulk lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…Renshaw et al [8] reported the η trend as a function of doping peaks for front surface field (FSF), back surface field (BSF) and emitter. Kim et al [9] studied some FOM as a function of geometrical parameters. In both works, FOM trends are evaluated for different surface recombination velocities (SRV) and bulk lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…For thick Si solar cells with the all-back-contact design, the pitch is normally 4400 mm, which allows less complicated fabrication processes such as screen-printing of metal contacts [38][39][40] . Previous studies have found that the fill factor (FF) was the only parameter that depended on the pitch in thick Si solar cells 41,42 . We, however, found that the J SC as well as the FF was closely dependent on the pitch in thin Si solar cells.…”
mentioning
confidence: 99%
“…1, J SC can be increased and the efficiency will be enhanced to 23.8%. Also the dimension of pitches, total of p-plus n-strips, can be optimized, where for traditional diffused IBC cells, the cell efficiency increases by 10% as pitch dimensions decreases from 1.7 mm to 600 μm [6]. Similar trends should also be valid for IBC-SHJ solar cells.…”
Section: Improving Ff For S-shape J-vmentioning
confidence: 89%
“…In this paper, we use "Sentaurus Device" [5], which is a simulator from software package Synopsys TCAD. Sentaurus Device is extensively used for modeling opto-electronic devices, and it is well suitable for modeling solar cells [6]. The latest version includes complex defect models allowing the simulation of devices which include amorphous silicon.…”
Section: Two-dimensional Modellingmentioning
confidence: 99%